Syncopations : the stress of innovation in contemporary American poetry - Rasula, Jed (University of Alabama Press, 2004)
Makes a case for innovation as the generative and thematic force in American poetry of the late 20th century. Syncopations is an analysis of the sustaining vitality behind contemporary American poetry from 1975 to the present day by one of the most astute observers and critics in the field. The 12 essays reflect Jed Rasula's nearly 30 years of advocacy on behalf of "opening the field" of American poetry. From the Beats and the Black Mountain poets in the 1950s and 1960s to the impact of language poetry, the specter of an avant-garde has haunted the administrative centers of poetic co
Keywords: American poetry -- 20th century -- History and criticism.; Experimental poetry, American -- History and criticism.; Poésie américaine -- 20e siècle -- Histoire et critique.; Poésie expérimentale américaine -- Histoire et critique.; POETRY -- American -- General.; American poetry; Experimental poetry, American; 1900-1999; Criticism, interpretation, etc.